Highlights of Magnetoelectropolishing - Hryniewicz, Tadeusz; Rokosz, Krzysztof (Frontiers in Materials, 2014)
The research work has been concerned on the studies and development of electrochemical polishing in the magnetic field (MEP) in comparison with the standard electropolishing methods performed without stirring (EP) and the process with the forced electrolyte mixing (MIX). Advanced techniques were used in the studies, to measure the effects of the surface treatment. They are as follows: scanning electron microscopy (SEM/EDS), X-ray Photoelectron Spectroscopy (XPS), Secondary Ion Mass Spectroscopy (SIMS), surface roughness, and nanoindentation measurements. For the corrosion studies, the electrochemical methods were used, such as: open circuit potential OCP, potentiodynamic curves PC, and electrochemical impedance spectroscopy EIS measurements. The MEP process is advised mainly due to the opportunity to enrich the surface layer with the chromium compounds (austenitic stainless steels), or titanium compounds (CP Ti Grade 2, Nitinol). The surface layers of biomaterials after MEP process contain much lower amount of carcinogenic compounds, like chromium VI oxidation stage (Cr6+) (austenitic stainless steels) and nickel compounds (austenitic stainless steel & Nitinol) versus those ones obtained after EP & MIX treatments. It is interesting that apart from the significant modification of the surface layer obtained after MEP, also mechanical properties, such as nanohardness, modulus of elasticity, and mechanical resistance to bending and torsion, undergo considerable advantageous changes. All they make the MEP process very promising for application in many clean industries, such as medical equipment and devices, electronics, food industry, etc.